Mutant forms of EGFR promote HER2 trafficking through efficient formation of HER2-EGFR heterodimers. (January 2023) - Tsutsumi, Hirono; Iwama, Eiji; Ibusuki, Ritsu; Shimauchi, Atsushi; Ota, Keiichi; Yoneshima, Yasuto; Inoue, Hiroyuki; Tanaka, Kentaro; Nakanishi, Yoichi; Okamoto, Isamu
Highlights: HER2 forms heterodimers with EGFR in cell lines without HER2 amplification. HER2-EGFR heterodimers are abundant in cell lines with EGFR mutations. HER2 is rapidly internalized as a result of its heterodimerization with EGFR. HER2 is efficiently transferred to lysosomes in cells with EGFR mutations. T-DM1 shows high cytotoxic efficacy in cells with EGFR mutations. Abstract: Introduction: Human epidermal growth factor receptor 2 (HER2) forms homodimers and is retained at the surface of cancer cells positive for HER2 amplification. The dimerization, internalization, and intracellular trafficking of HER2 in cancer cells without HER2 amplification have remained uncharacterized, however. Materials and methods: HER2 homodimers and heterodimers were detected in various cell lines with the use of an in situ proximity ligation assay. The effects of wild-type or mutant forms of epidermal growth factor receptor (EGFR) on intracellular trafficking of HER2 were examined by live-cell imaging. The sensitivity of cell lines without HER2 amplification to ado-trastuzumab emtansine (T-DM1), an anti-HER2 (trastuzumab)–cytotoxic drug conjugate (ADC) was also investigated. Results: HER2 preferentially formed heterodimers with EGFR rather than homodimers and was rapidly internalized together with EGFR in cells without HER2 amplification. HER2-EGFR heterodimers were more abundant and HER2 was more efficiently transferred to lysosomes in such cells with than in those without EGFR activating mutations. T-DM1 showed a high cytotoxic efficacy in the cells with EGFR mutations, suggesting that mutant forms of EGFR promote the transfer of HER2-bound T-DM1 to lysosomes through efficient formation of HER2-EGFR heterodimers. Conclusion: Our findings reveal that HER2 trafficking is affected by EGFR, especially by mutant forms of the receptor, and they provide a rationale for the use of HER2-targeting ADCs in the treatment of EGFR -mutated lung cancer.